Trends of Hypercholesterolemia Change in Shenzhen, China During 1997–2018 - Peng, Ke; Cai, Weicong; Liu, Xiaoying; Liu, Yishu; Shi, Yu; Gong, Jessica; Lei, Lin; Peng, Ji; Xie, Yuxin; Zhao, Honglei; Si, Lei; Ouyang, Menglu (Frontiers in Public Health, 2022)
To demonstrate the trends of hypercholesterolemia change in Shenzhen, China from 1997 to 2018. Participants were residents aged 18 to 69 years in Shenzhen, China and were recruited using multi-stage cluster sampling. All participants were surveyed about their socio-demographic, lifestyle, occupation, mental health and social support. Physical measurements and blood samples for subsequent measurements were collected according to a standardized protocol. A total of 26621 individuals participated in the three surveys with 8266 in 1997, 8599 in 2009 and 9756 in 2018. In both women and men, there was a significant downward linear trend in age-adjusted mean high-density lipoprotein-cholesterol (HDL-C) from 1997 to 2018 (women: 0.17±0.06, p=0.008 vs. men: 0.21±0.04, p<0.001). In contrast, the age-adjusted total triglycerides and total cholesterol in both sexes, demonstrated an increasing trend in the past two decades. However, no significant changes of age-adjusted low-density lipoprotein-cholesterol (LDL-C) in both men and women between 2009 and 2018 were found (women: 0.00±0.02, p=0.85 vs. men 0.02±0.03, p=0.34). The age-adjusted prevalence of hypercholesterolemia observed a rapid rise from 1997 to 2009 and appeared to be stabilized in 2018, which was similar to the trend of the prevalence of high total triglycerides in women. Changes in trends were varied by different types of lipids traits. There was a clear increasing trend of prevalence of low HDL-C (<1.04 mmol/L) in both sexes over the observed decades (women: 8.8% in 1997 and doubled to reach 17.5% in 2018 vs. men was 22.1% in 1997 and increased to 39.1% in 2018), particularly across younger age groups. Hence, a bespoke public health strategy aligned with the characteristics of lipids epidemic considered by sex and age groups is needed to be developed and implemented.